PENGARUH PEMBERIAN BAHAN HUMAT DAN KOMPOS SISA TANAMAN TERHADAP SIFAT FISIK TANAH DAN PRODUKSI UBI KAYU - Dwi Putro Tejo Baskoro (Jurnal Ilmu Tanah dan Lingkungan, 2010)
A study about the effect of humic substance and green manure on soil physical characteristics and cassava production was conducted on a Sandy loam soil in Sukadana-East Lampung. Humic substance was obtained from Proper Humic, whereas green manure was obtained from crop residue and weed surrounding the experimental site. Humic substance applied was 15 liters ha-1 and green manure applied was 2 tons ha-1. The result of the experiment indicated that in general, humic substance and green manure applied had no significant effect on soil physical characteristics. However, there was a tendency that water content at field capacity (pF 2.54) and water available capacity increased as humic substance and green manure were applied. Similar tendency was also observed for water retained in soil where field soil water content at 7 consecutive no-raindays was slightly higher at soil with humic substance and green manure. With the application of humic substance and green manure, soil could hold water in a longer time. The effect of green manure on field soil water content was, however, slightly better than that of humic substance. Nevertheless, application of humic substance 15 l ha-1 increased significantly cassava growth and production and the effect was better than those from green manure with the dosage of 2 ton ha-1. Key words: cassava production, humic substance, water retention